CodeOR: Opportunistic routing in wireless mesh networks with segmented network coding - Yunfeng Lin; Baochun Li; Ben Liang (2008 IEEE International Conference on Network Protocols, 2008)
Opportunistic routing significantly increases unicast throughput in wireless mesh networks by effectively utilizing the wireless broadcast medium. With network coding, opportunistic routing can be implemented in a simple and practical way without resorting to a complicated scheduling protocol. Due to constraints of computational complexity, a protocol utilizing network coding needs to perform segmented network coding, which partitions the data into multiple segments and encode only packets in the same segment. However, existing designs transmit only one segment at any given time while waiting for its acknowledgment, which degrades performance as the size of the network scales up. In this paper, we propose CodeOR, a new protocol that uses network coding in opportunistic routing to improve throughput. By transmitting a window of multiple segments concurrently, it improves the performance of existing work by a factor of two on average (and a factor of four in some cases). CodeOR is especially appropriate for real-time multimedia applications through the use of a small segment size to decrease decoding delay, and is able to further increase network throughput with a smaller packet size and a larger window size.